Cash the Trash - Nagargade, Mona; Shukla, S K; Pathak, A D (Indian Farming, 2021)
Sugarcane crop produces a huge quantity of residue (green leaves, dry leaves, and green top) afterharvesting of cane. The common practice of farmers is either burning or removal of the cropresidues from the field. The removal of trash from the field is a labor and time-intensive process.Rampant burning of trash to clean the field is the only solution in front of farmers. There is aneed to convert waste into wealth to provide an alternative to residue burning. Sugarcane trashcan produce series of value-added chemicals besides its field application. Field application of trashin the form of mulching enriches the soil organic carbon pool besides conserving essential elements.Trash mulching improves soil’s organic carbon content and ultimately, after recycling, addnutrient into the soil. Efficient utilization of trash reduces environmental pollution, sustains soilhealth, and provides economic gain to the farmers.